2016
DOI: 10.1186/s12891-016-1326-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrotic action of pirfenidone in Dupuytren’s disease-derived fibroblasts

Abstract: BackgroundDupuytren’s disease (DD) is a complex fibro-proliferative disorder of the hand that is often progressive and eventually can cause contractures of the affected fingers. Transforming growth factor beta (TGF-β1) has been implicated as a key stimulator of myofibroblast activity and fascial contraction in DD. Pirfenidone (PFD) is an active small molecule shown to inhibit TGF-β1-mediated action in other fibrotic disorders. This study investigates the efficacy of PFD in vitro in inhibiting TGF-β1-mediated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…Our data clearly showed an upregulation of phosphorylated SMAD2/3 in response to TGF-β1 stimulation, although PFD did not affect this response at any dose or time tested (0.1, 0.5, or 1.0 mg/mL from 5 to 60 min after TGF-β1 stimulation). This contrasts previous findings of PFD inhibition of SMAD phosphorylation in TGF-β1-stimulated human lung fibroblasts and Dupuytren's disease-derived fibroblasts [27,52]. This difference in PFD action may be due to differences in fibroblasts sourced from different tissues, disease states, and in vitro culture systems [56][57][58].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Our data clearly showed an upregulation of phosphorylated SMAD2/3 in response to TGF-β1 stimulation, although PFD did not affect this response at any dose or time tested (0.1, 0.5, or 1.0 mg/mL from 5 to 60 min after TGF-β1 stimulation). This contrasts previous findings of PFD inhibition of SMAD phosphorylation in TGF-β1-stimulated human lung fibroblasts and Dupuytren's disease-derived fibroblasts [27,52]. This difference in PFD action may be due to differences in fibroblasts sourced from different tissues, disease states, and in vitro culture systems [56][57][58].…”
Section: Discussioncontrasting
confidence: 91%
“…While the exact mechanism(s) of PFD remain unknown, previous studies demonstrated its effectiveness at mitigating myofibroblast differentiation, proliferation, and profibrotic cytokine production in both in vitro and in vivo models of lung, liver, and renal fibrosis [22,23]. The potential of PFD as a topical therapeutic agent for use during wound healing [24,25] or following HTS development [26] has been suggested, however the mechanism by which PFD exerts its antifibrotic properties on dermal cells has not been fully described [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In a study done on PFD in malignant mesothelioma, it was shown that PFD reduced the TGF-β-induced extracellular-signal-regulated kinase (ERK) and serine/threonine-specific protein kinase (AKT) pathways [ 19 ]. Not only did PFD reduce the proliferation of cells in mesothelioma, but also it reduced the proliferation of fibroblasts derived from Dupuytren's disease in another study done in vitro [ 19 , 20 ]. The Smad2 phosphorylation induced by TGF-β1 was down-regulated in Dupuytren's disease derived-fibroblasts (DD-fibroblasts); hence PFD acted through the canonical Smad signaling pathway at least partially [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…Not only did PFD reduce the proliferation of cells in mesothelioma, but also it reduced the proliferation of fibroblasts derived from Dupuytren's disease in another study done in vitro [ 19 , 20 ]. The Smad2 phosphorylation induced by TGF-β1 was down-regulated in Dupuytren's disease derived-fibroblasts (DD-fibroblasts); hence PFD acted through the canonical Smad signaling pathway at least partially [ 20 ]. While in the study of malignant mesothelioma, the canonical Smad pathway was not affected [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…It has already been described that therapies preventing the contraction of myofibroblasts could prevent the contraction and subsequent continuous remodeling of ECM [31]. Pirfenidone [32] acts at this level, inhibiting the functions mediated by TGFß-1 in the cells. 5-fluorouracil has also been tested in DC at this level, reducing the fibroblast and myofibroblast differentiation ratios and their contractility [33].…”
Section: Association and Action Timementioning
confidence: 99%